The effects of explosive loads on structures - Zhan, Hui Hui (2018)
This report investigates the effects of explosive loads on structural panels. The blast waves from the explosion which is a series of pressure waves could lead to various structural responses on the structure. This project simulates and studies the explosion-induced structural responses via simple plate panels with diverse geometric parameters and varying proximity to the centre of an explosion. The conventional engineering software, ANSYS APDL, is used for the analysis of explosion effects. The physical properties of S355 steel are applied in the simulation. As the primary outcome of an explosion are the pressure waves on nearby structures and they could cause structural damages due to large deformation. With simulated finite element analysis (FEA), the structural responses on the numerical models are analytically determined as the transient time history. In this report, the simulation runs include the following: firstly, the types of pressure waves and the severity of structural damage in relation to the distance of structure to the centre of explosion; secondly, the extent of pressure wave on the plate panel; thirdly, the geometric parameters of the plate such as the thickness, length and width, and its boundary conditions.The results of numerical simulations for explosion-induced waves indicate that structural responses are linear dependence to distances from structural panel to centre of an explosion. Meanwhile, the simulated results show structural responses are inversely proportional to the thicknesses cube of the structure. Furthermore, the relative thinner plate increases the relatability of verdict from test data. In addition, different dispersals of pressure loadings also exist variant distinctions of structural deformation. Other minor effects are discussed in the report.